Aphid and caterpillar feeding drive similar patterns of induced defences and resistance to subsequent herbivory in wild cotton - Teresa Quijano-Medina; Jonathan Interian-Aguiñaga; Uriel Solís-Rodríguez; Mamin, Marine; Clancy, Mary; Ye, Wenfeng; Bustos Segura, Carlos; Marta Francisco; José A. Ramos-Zapata; Turlings, Ted; Xoaquín Moreira; Luis Abdala-Roberts (My University, 2023)
Plant-induced responses to attack often mediate interactions between different species of insect herbivores. These effects are predicted to be contingent on the herbivore’s feeding guild, whereby prior feeding by insects should negatively impact subsequent feeding by insects of the same guild (induced resistance) but may positively influence insects of a differ- ent guild (induced susceptibility) due to interfering crosstalk between plant biochemical pathways specific to each feeding guild. We compared the effects of prior feeding by leaf-chewing caterpillars (Spodoptera frugiperda) vs. sap-sucking aphids (Aphis gossypii) on induced defences in wild cotton (Gossypium hirsutum) and the consequences of these attacks on subse- quently feeding caterpillars (S. frugiperda). To this end, we conducted a greenhouse experiment where cotton plants were either left undamaged or first exposed to caterpillar or aphid feeding, and we subsequently placed caterpillars on the plants to assess their performance. We also collected leaves to assess the induction of chemical defences in response to herbivory. We found that prior feeding by both aphids and caterpillars resulted in reductions in consumed leaf area, caterpillar mass gain, and caterpillar survival compared with control plants. Concomitantly, prior aphid and caterpillar herbivory caused similar increases in phenolic compounds (flavonoids and hydroxycinnamic acids) and defensive terpenoids (hemigossypolone) compared with control plants. Overall, these findings indicate that these insects confer a similar mode and level of induced resistance in wild cotton plants, calling for further work addressing the biochemical mechanisms underpinning these effects.
Projet FNS : https://data.snf.ch/grants/grant/185319
Keywords: Aphis gossypii; Phenolics; Plant-mediated interactions; Sequential herbivory; Spodoptera frugiperda; Terpenoids